Application of colloidal dispersions on the basis of silicon dioxide in the building - Gaishun, В. Е.; Tyulenkova, О. И.; Kosenok, Я. А.; Matyuha, С. Л.; Kadol, Владимир Федорович (Chrezvychaynye situatsii: obrazovanie i nauka, 2007)
For today in Republic Belarus in quality laggings as on industrial objects, so in individual houses the combustible matters will be used, which one at hit even of subcaloric sources of ignition easily ignite, that results in fires and considerable material damage, instead of is rare also to human victims. In this connection now there is a problem of maintenance of more effective protection industrial and utility spaces. We establishment new ultra dispersed suspension on the basis of pyrogenic silicon dioxide which can be used as inorganic additives for introduction in structure binding heat isolation plates on the basis of basalt fibres.